CAPITAL ADEQUACY RATIO ANALYSIS FOR BANK BUSINESS ACTIVITY GROUP 3 AND GROUP 4 IN INDONESIA FOR PERIOD 2011-2017 - Herlina 29116237, Listri
ABSTRACT Since the global financial crisis began, capital adequacy ratio (CAR) of a bank into the spotlight due to the crisis undoubtedly indicates that existing capital arrangements are inadequate to prevent panic in the financial sector. Regulators, which act on behalf of governments, require the capital to be above a prescribed minimum level. According to central bank regulation, banks are required to raise capital that exceeds the minimum capital ratio as a buffer against potential losses, Also, by increasing capital, banks will be more confident in improving business performance. This study analyzes how the capital condition of 14 commercial banks in the category of bank business activity group 3 and group 4 that listed on IDX. The analysis is related to central bank regulation concerning banks are required to increase capital more than the minimum capital adequacy ratio as a buffer. The analysis use panel data regression method to analyze the dependent variable and independent variables. Six independent variables used from internal financial factors, namely non-performing loan (NPL), net interest margin (NIM), loan to deposit ratio (LDR), credit growth (CG), operating expense to operating income (BOPO) and risk-weighted assets (RWA).The estimation result found that NPL and BOPO significantly affect the capital of 14 Bank and the result shows that three banks have the highest capital adequacy ratio (CAR). Furthermore, there are three banks with the lowest capital adequacy ratio.